Forests and Their Canopies: Achievements and Horizons in Canopy Science - Nakamura, Akihiro; Kitching, Roger L; Cao, Min; Creedy, Thomas J; Fayle, Tom M; Freiberg, Martin; Hewitt, C N; Itioka, Takao; Koh, Lian Pin; Ma, Keping; Malhi, Yadvinder; Mitchell, Andrew; et al. (Trends in ecology & evolution, 2017)
Forest canopies are dynamic interfaces between organisms and atmosphere, providing buffered microclimates and complex microhabitats. Canopies form vertically stratified ecosystems interconnected with other strata. Some forest biodiversity patterns and food webs have been documented and measurements of ecophysiology and biogeochemical cycling have allowed analyses of large-scale transfer of CO2, water, and trace gases between forests and the atmosphere. However, many knowledge gaps remain. With global research networks and databases, and new technologies and infrastructure, we envisage rapid advances in our understanding of the mechanisms that drive the spatial and temporal dynamics of forests and their canopies. Such understanding is vital for the successful management and conservation of global forests and the ecosystem services they provide to the world.
Keywords: biogeochemical cycle; lesy; stromy; Ecosystem; cranes; Trees; atmosféra; food webs; biodiversity; biodiverzita; Atmosphere; remote sensing; Forests; canopy; ekosystém; Biodiversity